The Effects of Usury Ceilings on Consumers Welfare: Evidence from the Microcredit Market in Colombia - Laura Capera Romero (Tinbergen Institute, 2021)
Interest rate caps, also called usury ceilings, are a widely used policy tool to protect consumers from excessive charges by loan providers. However, they are often cited as a barrier for the advancement of financial inclusion, as they may reduce the incentives to provide loans to lower-income borrowers and and to invest in branching networks, particularly in remote and isolated locations. In this paper, I exploit a change in the usury ceiling applied to micro-loans in Colombia to understand the effects of this policy across geographic markets. To quantify the welfare implications of this policy, I structurally estimate a demand and supply model that incorporates the changes in size and composition of the potential market caused by this policy change, in a context where the distribution of branching networks has a crucial role in the optimal pricing strategies of loan providers. I find that the policy generated an increase in consumer surplus at the national level that is explained by greater credit availability for riskier borrowers and the expansion of branching networks in areas that were previously under-served. A counterfactual exercise reveals that the welfare gains associated to this policy depend greatly on additional investment in branching networks, as the opening of new branches in some locations is needed to compensate the consumer welfare loss associated with the subsequent increase in interest rates after the relaxation of the ceiling.
Keywords: L11; D43; D61; G21; G28; 330; Microfinance institutions; price ceilings; consumer welfare